Correction of a postpneumonectomy syndrome with congenital pectus excavatum using Ravitch’s procedure and silicone breast implants. Report of a case - Essaleh, Weam (Int J Surg Case Rep, 2020)
INTRODUCTION: Mediastinal repositioning and the use of allogenic implants to obliterate the postpneumonectomy space is the main principle of postpneumonectomy syndrome (PPS) correction. We present a rare case with a PPS in combination with a congenital pectus excavatum. As a pectus excavatus deformity reduces retrosternal space, simple repositioning of the heart is impossible unless combined with a sternum elevation. PRESENTATION OF CASE: Two years after left sided pneumonectomy a 30 year old female was admitted with progressive exertional dyspnea and stridor and not able to do her basic activities. Chest CT-scan and bronchoscopy revealed severe right main bronchus stenosis, compression of hilar vessels and the presence of a pectus excavatum deformity. A single stage operative correction was performed with sternum repositioning by a Ravitch’s procedure, pericardial fixation to the right sternal edge and obliteration of the left thoracic cavity with two silicone breast implants. All complaints disappeared within 48 h. DISCUSSION: To the best of our knowledge, this is the first report about successful treatment of PPS aggravated by a preexisting pectus excavatum in an adult patient. The durability and migration of the silicone implants and the volume reduction of the pericardial sac during fixation to the sternum continues to remain a concern. CONCLUSION: Single stage correction of PPS and pectus deformity is feasible and seems to be the appropriate treatment for both pathologies.